Evaluation of anxiety, depression and stress symptoms in men with prostate cancer during the preoperative period (Bioscience Journal, 2020)
Prostate cancer is the second most common type of cancer among men, being considered a cancer of the elderly because about three quarters of cases worldwide occur in individuals aged 65 and over. Anxiety, depression and stress are three emotional states understood as psychological morbidity factors, and they interfere with the patient's adaptation to the diagnosis. The present study aimed to identify anxiety, depression and stress levels in men with prostate cancer, describing sociodemographic and clinical characteristics and investigating whether the influence of such characteristics on the emotional symptoms of patients is significant. Cross-sectional study with a quantitative approach performed in two public hospitals with patients preoperatively for prostatectomy. Two instruments were used, one covering sociodemographic and clinical aspects of the patients, and the other was the Depression Anxiety and Stress Scale (DASS-21)-Short Form. In the statistical analysis, the Pearson correlation test and the Mann-Whitney U test were used to evaluate the variables of interest, considering the significance level of 0.05. As a preliminary study, 31 patients were interviewed. The results indicated a predominant age of 60 years or older (72.4%), 71% of men had low level of education, and 51.6% did not have partner. The mean scores obtained in the DASS-21 were 2.84 (SD = 3.925) for depression; 3.68 (SD = 3.655) for anxiety; and 6.71 (SD = 6.92) for stress. The results revealed no significant correlation between these constructs and the variables of interest. However, a descriptive analysis of the data showed a minimal correlation of anxiety (r = 0.191) and stress (r = 0.149) with the numerical variable time since diagnosis. In conclusion, the results presented important questions related to prostate cancer diagnosis, involving patients' marital status, religion and cancer staging.